Exploring inbreeding depression in Brazilian Angus cattle population using pedigree and genomic data - Mulim, Henrique A.; Campos, Gabriel S.; Cardoso, Fernando Flores; Rojas de Oliveira, Hinayah (Frontiers in Genetics, 2025)
IntroductionInbreeding depression refers to the decline in performance caused by increased levels of inbreeding, which results from mating individuals with common ancestors. This study aimed to estimate inbreeding coefficients based on both pedigree and genomic information using six different metrics and evaluate, the inbreeding depression on different traits officially evaluated by the Brazilian Angus Association.Material and MethodsA total of 13,777 genotyped animals, imputed to a density of 78,837 SNPs, and 530,327 animals in the pedigree file, extending up to 17 generations, were used in the analysis. The inbreeding metrics evaluated included: pedigree-based inbreeding (FPED), genomic relationship matrix-based inbreeding (FGRM), observed vs. expected homozygosity (FHOM1), genotyped homozygosity (FHOM2), correlation between uniting gametes (FUNI), and runs of homozygosity (FROH). Traits related to growth, conformation, meat quality, reproduction, resistance to ectoparasites, and heat stress were analyzed.ResultsThe results revealed a range of inbreeding coefficients, with inbreeding estimated using ROHs showing the highest values (0.13). The impact of inbreeding on various traits was predominantly negative, with significant inbreeding depression observed for traits such as hair coat. Some traits, such as intramuscular fat and birth weight, had positive associations with inbreeding, indicating a complex trait-specific relationship. Shorter ROH segments (<2 Mb) generally had smaller or beneficial effects compared to longer ROH segments (>16 Mb).DiscussionThese findings underscore the complexity of inbreeding depression and highlight the importance of considering both the extent and historical depth of inbreeding when evaluating its effects on various traits. Overall, this research provides valuable insights into the genetic basis of inbreeding depression in the Brazilian Angus population and demonstrates the usefulness of genomic data in understanding and mitigating the impacts of inbreeding in livestock populations.